How to deliver a TED talk : secrets of the world's most inspiring presentations - Donovan, Jeremey (McGraw Hill-Ascent Audio, 2014)
DELIVER THE PRESENTATION OF YOUR LIFE--AND LAUNCH YOUR CAREER A nonprofit dedicated to ideas worth spreading, TED challenges the world's most fascinating thinkers and doers to give "the speech of their lives" in 18 minutes or less. The more than 14,000 talks on TED.com have been viewed over 1 billion times and include those by such luminaries as Tony Robbins, Dan Pink, and Sheryl Sandberg. Now you can learn how to give a TED-style talk to achieve your personal and business goals. How to Deliver a TED Talk provides more than 100 invaluable tips--everything from opening with an explicit statement of audience benefits to framing your idea as an action-outcome response to a question worth asking. Whether you're presenting to an audience of 1 or 1,000, this book is an indispensable resource for any public speaker. "Not just for TED talks, it's a great book for any presentation you have to make. If you want to deeply engage and impress your audience, this is a quick, informative, and brilliant guide."--PETER BREGMAN, TEDx talker and author of 18 Minutes "Jeremey's advice was key to my successful TED talk at TEDMED." -- AMANDA BENNETT, Pulitzer Prize-winning journalist and Executive Editor/Projects and Investigations for Bloomberg News